Submarine FREsh water dischargEs: characteriZation and Evaluation (Projecto FREEZE) - Carrara, Gabriela (2022)
ABSTRACT: The flow of terrestrial groundwater towards the sea is an important natural component of the hydrological cycle (Church, 1996). Hydrological studies have shown that land derived fresh groundwater may discharge through the sea floor through a process known as submarine groundwater discharge (SGD, Taniguchi et al., 2002). Many studies have highlighted the ubiquitous occurrence on the near-shore environment (Bratton, 2004) and for carbonate acquiferous (limestones or dolomite) with dissolution flow conduits discharge in the form of submarine freshwater springs is a well-known phenomenon (Moore, 2008; Taniguchi et al., 2002). In Portugal, groundwater supplies about 70% of the fresh water needs and most of the aquifers are hosted in sandstones and limestones along the Portuguese coastline where more than 60% of the whole population dwells. It is assumed in various cases that the aquifers discharge to the sea based on the hydraulic heads, geology and geometry of the aquifers, and on the results of numerical models. The identification and quantification of groundwater submarine discharge is crucial for water and ecosystem management. At present, the over-exploitation observed in the main deep aquifers located in the Beira-Litoral, SetúbalPeninsula and Algarve regions (north, centre and south of Portuguese littoral) led to the prohibition of drilling new boreholes, which limits local investment and economic development. The project FREEZE - Submarine FREsh water dischargEs: characteriZation and Evaluation study on their impact on the Algarve coastal ecosystem (PTDC/MAR/102030/2008) is a Portuguese national research project funded by FCT. The project started officially in January 2010 and was devoted to the study of the freshwater submarine groundwater discharges (SGD's) at sea off Olhos de Água area (Algarve, South Portugal). The project focused part of its activity on mapping an area in the continental shelf where SGDs are known to occur in the intertidal zone and their monitoring; a remote sensing methodology for detection of SGDs in the offshore have been tested leading to shallow water physical oceanographic parameters acquisition. Estimation of freshwater SGD respect to the local groundwater reserves was another key project aim in the scope to evaluate a possible exploitation or to increase attention to the monitoring of present boreholes exploitation in the studied area. In addition particular attention was dedicated to the analysis and monitoring of the submarine ecosystems and biological communities associated to the discovered SGDs. To achieve all these goals a multidisciplinary team of geologists, geophysicists, oceanographers, hydro-geologists, geochemists and biologists has been gathered in the scope to collaborate approaching the same topic by different point of view. Most of the time, the various investigations/activities have been strictly connected one to each other assuring an immediate feedback and helping in this way to the planning of further initiatives.